2015
DOI: 10.18632/oncotarget.6559
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases antitumor activity of MEK inhibitors through GLI1 downregulation in LKB1 positive human NSCLC cancer cells

Abstract: PurposeMetformin, widely used as antidiabetic drug, showed antitumoral effects expecially in combination with chemotherapy. Our group recently has demonstrated that metformin and gefitinib are synergistic in LKB1-wild-type NSCLC cells. In these models, metformin as single agent induced an activation and phosphorylation of mitogen-activated-protein-kinase (MAPK) through an increased C-RAF/B-RAF heterodimerization.Experimental designSince single agent metformin enhances proliferating signals through the RAS/RAF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 41 publications
0
54
1
Order By: Relevance
“…A study by Kim et al (7) reported that diabetic patients with no administration of insulin had a decreased incidence of gastric cancer when treated with metformin, compared with those who were not treated with metformin. Another previous study showed that the use of metformin as a single agent induced the activation and phosphorylation of mitogen-activated-protein-kinase through the increased heterodimerization of C-RAF/B-RAF in non-small cell lung carcinoma cells (17). In addition, it has been demonstrated that the duration of metformin treatment is associated with the decreased risk of gastric cancer, particularly in patients who used metformin for >3 years (7).…”
Section: Discussionmentioning
confidence: 98%
“…A study by Kim et al (7) reported that diabetic patients with no administration of insulin had a decreased incidence of gastric cancer when treated with metformin, compared with those who were not treated with metformin. Another previous study showed that the use of metformin as a single agent induced the activation and phosphorylation of mitogen-activated-protein-kinase through the increased heterodimerization of C-RAF/B-RAF in non-small cell lung carcinoma cells (17). In addition, it has been demonstrated that the duration of metformin treatment is associated with the decreased risk of gastric cancer, particularly in patients who used metformin for >3 years (7).…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports in tumours suggested that metformin could inhibit cell migration and invasion by suppression of MMP-9 [47][48][49]. A study in skin tissue showed that metformin significantly inhibits MMP-9 expression and protect collagen degradation from solar ultraviolet radiation [50].…”
Section: Discussionmentioning
confidence: 99%
“…LKB1 interacts with AKT (33), and can facilitate AKT activation and enhance its antiapoptotic effects (33,34). LKB1 and AMPK also exhibit cross talk directly with RAS/RAF/MEK signaling pathways (35,36), in which MEK phosphorylates LKB1, leading to LKB1 and AMPK attenuation, whereas AMPK activation potentiates RAS/RAF/MEK signaling (37). Thus, in LKB1 wild-type cells, metformin and MEK inhibition demonstrate synergistic anticancer effects (37).…”
Section: Discussionmentioning
confidence: 99%
“…LKB1 and AMPK also exhibit cross talk directly with RAS/RAF/MEK signaling pathways (35,36), in which MEK phosphorylates LKB1, leading to LKB1 and AMPK attenuation, whereas AMPK activation potentiates RAS/RAF/MEK signaling (37). Thus, in LKB1 wild-type cells, metformin and MEK inhibition demonstrate synergistic anticancer effects (37). These various pathways exhibit complex feedback and autoregulation, and further studies of these signaling networks will inform understanding of drug sensitivity phenotypes and improve treatment, for example, through the rational design of combinatorial approaches to overcome resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%